Voices, Subjectivities and Desires. Costa Rican Secondary Teachers’ and Students’ Discourses About Sexual Diversity - Fernández Fernández, Daniel (2020)
This paper takes the experiences and opinions of Costa Rican teachers and students about sexual diversity as a source of analysis. With the aim of decoding these discourses, queer pedagogy is understood as a theoretical reading tool that allows to display the reification of normality. More precisely, the chapter proposes a queer analytic of the limits of intelligibility of teachers’ and students’ discourse. The focus, then, will not be “what do teachers and students actually think?”, but “what enables them to think what they actually think?” At the same time, the analysis also helps to stress the contrast between the discourse of those who transgress normality and those who are placed in a position of guarantors of the status quo.